PENGARUH PENERAPAN PERMAINAN SUCKER BALL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 33 PADANG TAHUN PELAJARAN 2013/2014 - Maryuliasti, Nices; Zulfaneti, Zulfaneti; Lovia, Lita (Pendidikan Matematika, 2014)
This research was backgrounded by students understanding on mathematic concepts was low. This research was aimed to see what is the students understanding on mathematic concept by using Sucker Ball game better than the students understanding on mathematic concept by using conventional learning at Eighth grade students of SMPN 33 Padang academic year 2013/2014. This study was experimental research by random selecting group of sample. The technique of data nalysis used t-test by using MINITAB. Refering to the data analysis that had been clone it was found P-value = 0,042 was lower than Î± = 0,05. It can be summarized that the student understanding on mathematic concept using Sucker Ball game better than the student understanding on mathematic concept using conventional learning.